ENVIRONMENTAL PROTECTION AND MANAGEMENT IS THE LEGAL BASIS FOR ENVIRONMENTAL CRIMES IN INDONESIA - Idrus, Wahyuni; Hafid, Zhulfiana Pratiwi; Rahman, Ali (International Peneliti Ekonomi, Sosial dan Teknologi, 2024)
Environment life moment This is one of the most common problems debated in the world. Because of the impact bad caused? man to environment life, condition environment life moment This become threat for existence humans in the future. In Indonesia, at the moment This anyone or? any group that does action destruction environment is action illegal. Terms the in a way general referred to in the 1945 Constitution and related regulations? with environment life. Implementation and enforcement law environment living in Indonesia, violation formal and material found? in Constitution Number 32 of 2009, and influence law environment life to other things are just a number of problem environment life that will try under review in journal.